Izbrana zdravila naravnega izvora za zdravljenje bolezni ORL - Kreft, Samo (Farmacevtski vestnik, 2012)
Medicinal plants are very often used to treat diseases of ears, nose and throat. Most indications are related to cough and inflammation and wounds of oral mucosa and their efficiency is plosable and based on tadicionalne use. These indications are systematically discussed in the the so called herbal monographs of the European Communities. There are fewer indications where efficacy is based on the clinical studies of high quality. In this paper we discuss recent research on the use of ginkgo for tinnitus, and two Slovenian clinical trials: Hederae folium and a combination of 5 herbs (elder (Sambucus nigra) flowers, primrose (Primula veris) flowers with calyx, common sorrel (Rumex acetosa) herb, European vervain (Verbena officinalis) herb and gentian (Gentiana lutea) root) for acute respiratory infection.
Keywords: ginko; otolaringologija; tinitus; zdravila naravnega izvora; zdravilne rastline